Guided morphogenesis through optogenetic activation of Rho signalling during early Drosophila embryogenesis - Emiliano Izquierdo (Nature Portfolio, 2018)
Optogenetics is opening the possibility to not only perturb morphogenesis, but also to guide it. Here, the authors use this technique to reconstruct epithelial folding in Drosophila embryos and study the relationship between strength of Rho activation, apical constrictions, and tissue invagination.